Controle do crescimento vegetativo e floração de mangueiras cv. Kent com reguladores de crescimento vegetal - do Carmo Mouco, Maria Aparecida; Ono, Elizabeth Orika [UNESP]; Rodrigues, Joao Domingos [UNESP] (Soc Brasileira Fruticultura, 2011)
Paclobutrazol applied to the soil is used for the production management of mangoes in most of the orchards, but it presents as disadvantage the greater persistence in plant and soil. Three growth regulators (prohexadione-Ca, trinexapac-ethyl and chlormequat chloride) were foliar applied, at two dosages and compared to paclobutrazol applied as soil-drench. The experiment was conducted in the region of the Sao Francisco Valley, Petrolina, PE, from December 2007 to July 2008, in a mango orchard that has a spacing of 8 m between lines and 5 m between plants. In order to compare the effects of the treatment, data were evaluated regarding to vegetative growth (number, length and leaf number of vegetative branches) and flowering (percentage and panicles length). The combination of PBZ, soil applied with ProCa, foliar applied was the most efficient in controlling vegetative growth of branches of the mango 'Kent', but not regarding to flowering, where there were no differences between treatments.
Control of vegetative growth and flowering on Mango cv. kent with plant growth regulators
Keywords: gibberellin; prohexadione-Ca; trinexapac-ethyl; chlormequat chloride